Experiences in the application of a triage system in the health institutions of the province of Cienfuegos, 1998-2016 - Víctor René Navarro Machado; Arelys Falcón Hernández; Omar Bárbaro Rojas Santana; Raúl Nieto Cabrera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: Having a triage system is essential for emergency systems, given the high demand for assistance and the need to offer quality medical care. Objective: to describe the system of triage developed at the Cienfuegos Province between 1988 and 2016. Methods: research in systems and health services, mixed in methods and techniques, which included the 24 emergency services of the territory. Indicators in the records of the health institutions were included and the results of other research conducted during the period, which also measured them. Results: atriage system was designed with three coding levels (red, yellow and green) according to vital risk. The red code was similar for the entire healthcare network. Main indicators: average time of arrival-triage 2.5 minutes; duration of the triage <5 min; arrival time-medical attention (red 0-7 minutes, yellow 7-14 minutes, green 28 minutes); percentage of patients attended but not classified 10.5%; agreement index between nurse-sorter and doctors for patients with green or yellow code 77.6%; percentage of income for patients with a red code, 98%; percentage of income for patients with a yellow code of 19.5%. In the period under review, the demand for medical care doubled (mainly due to the green code), and the mortality rate of the emergency department was reduced. Conclusion: The triage system in Cienfuegos is structured, is useful and has been effective mainly for the most serious adult patients.